Edge Signal Domination In Some Transformation Graphs - Samuel. S, Jachin; Kavitha Raj, S. Angelin (Journal of Neonatal Surgery, 2025)
The concept of domination is an important part of graph theory. The edge signal domination is a parameter that takes into account the degree of vertices as well as the edge coverage in graphs which are crucial in the field of networking. Transformation graph is a concept in mathematics that primarily focuses on the structural change and behavior by applying graph-theoretic transformations to the graphs. It is mainly used in fields like computational modelling, biological model systems and other fields. In this article, we rely on the edge signal domination parameter and identify the parametric values for three distinct operations on graphs namely line graph, middle graph and corona product in some common graph families.